Comparison of Antimicrobial Efficacy of Calcium Hydroxide and 2% Chlorhexidine as Medicaments - Tripathi, Rupan; Gautam, Vanita; Pahwa, V. K.; Agrhari, Vikas; Batra, Manu; Kumar, Hemant (Journal of Universal College of Medical Sciences, 2018)
INTRODUCTION: The use of intracanal medicaments help in elimination of bacteria that remain even after cleaning and shaping. This study isdone to compare the antimicrobial efficacy of2% chlorhexidine gel and calcium hydroxide as an intracanal medicament against E.faecalis. MATERIAL & METHODS: Sixty extracted single-rooted human teeth were prepared with standard method. After contaminating the canals with E. Faecalis and incubated for seven days, the samples were divided into four groups (n=15). Normal saline was used as control group. The teeth in each group were treated with normal saline, calcium hydroxide and 2% chlorhexidine gel. Microbial samples were obtained from the dentinal shavings of root and colony forming units (CFU) of E.faecalis were recorded after 24hrs, 72hrs and 7 days. RESULTS: To determine the significance of the differences between the different groups, ANOVA(Analysis of variance) and Tukeys Honestly significant Difference (HSD) Post hoc test were performed. Mean CFU of calcium hydroxide group and 2% chlorhexidine group was statistically significantly different from CFU of all other groups (p<0.01). CONCLUSION: Mean CFU of calcium hydroxide was found to increase at 24 hrs and decreases at 72 hrs and 7 days.The antimicrobial efficacy 2% chlorhexidine gel was better than calcium hydroxide paste. Journal of Universal College of Medical Sciences (2017) Vol.05 No.02 Issue 16, Page: 8-11